Abdominopelvic impalement with tree branch causing major vascular injury - Stevan Fairburn; Adam Sturdivant; James Hwang; John B. Holcomb; Jeffrey D. Kerby; Janet Julson; Jon Winkler; W. Preston Hewgley (Trauma Case Reports)
This case report describes the management of a 45-year-old female who sustained an abdominopelvic impalement injury from a tree branch following a motor vehicle accident. The branch impaled the abdominal wall at the left lower quadrant and exited the patient's left posterior pelvis. The impaled object prevented supine positioning and disrupted the formulaic primary and secondary survey. While tempting to remove such an impaled object, surgical fundamentals dictate they be left in situ until surgical intervention. In this scenario, tamponade from the impaled object prevented catastrophic hemorrhage until vascular control was established in the operating room. The patient's physiology remained appropriate to begin reconstructive efforts at the index operation, minimizing the number of operations and ensuring the patient's long-term functionality. Management of this impaled object provides an example of how to manipulate the surrounding environment to optimize surgical approach when external factors prevent standard positioning.